catena-Poly[bis(sulfamethoxazolium) [[trichloridocadmate(II)]-μ-chlorido] monohydrate] - Subashini, Annamalai (International Union of Crystallography, 2007)
In the title compound, {(C(10)H(12)N(3)O(3)S)(2)[CdCl(4)]·H(2)O}(n), the Cd(II) atom is five-coordinate with a distorted trigonal–bipyramidal geometry formed by chloride ions. The Cd atom and two of the Cl atoms lie on a mirror plane. The cation is protonated on the amino group N atom; it is not coordinated to cadmium, but is hydrogen bonded to the chlorido ligands. Each water molecule bridges two chlorido ligands, generating ring motifs along the –Cd—Cl—Cd– chains. The isoxazole unit and the amide groups are linked through a pair of N—H⋯N hydrogen bonds. The crystal structure is stabilized by N—H⋯O, O—H⋯Cl, C—H⋯N, N—H⋯Cl and C—H⋯O hydrogen bonds.